HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN SELF ESTEEM PADA REMAJA AKHIR DI KOTA DENPASAR - Sancaya, Anak Agung Gede Ariputra; Susilawati, Luh Kadek Pande Ary (Jurnal Psikologi Udayana; Edisi Khusus, 2014)
Adolescent development toward the adult stage is always in touch with the family in every aspect. One aspect is the development of adolescent self-esteem. Self esteem is one of the aspects that support the development of adolescents to be able to develop optimally and determine success in adulthood. Adolescents need the support of the family to be able to develop self-esteem because the family is the first social environment where adolescents develop. Therefore, researchers assume that there is a relationship between family social support with self-esteem in adolescents in the city of Denpasar. This research method is quantitative correlation where the number of the subject in Denpasar 408 teenagers whose age 17-19 years . Methods of data collection is family social support scale and the scale of self esteem . Reliability of family social support scale is 0.943 and self esteem scale reliability is 0.940 . Normality of families social support variable is 0,219 and self-esteem variables normality is 0.572 . Linearity between family social support variables and self esteem is 0,000 . The coefficient of determination ( r2 ) 0.268 . Methods of data analysis is a technique of regression. The correlation coefficient is 0.518 with a probability of 0.000 . It is proved that there is a correlation between social support families with self-esteem in adolescents in the city of Denpasar.   Keywords: family social support, self esteem, adolescents